Impact of heat on dental structures and DNA recovery in forensic science: a systematic review - Ana María Salazar Roa (Egyptian Journal of Forensic Sciences, 2025)
Abstract Background Teeth play a vital role in forensic identification due to their durability and exceptional ability to preserve DNA, even under extreme environmental stress. Among the hardest structures in the human body, dental tissues such as enamel, dentin, and cementum offer significant protection to genetic material thanks to their high mineral content and structural resilience. This systematic review aims to synthesize current evidence on the effects of thermal stress on human dental structures and DNA preservation, highlighting the underlying molecular damage mechanisms and evaluating their forensic implications, with the goal of providing clearer guidance and laying the groundwork for optimizing DNA recovery protocols from heat-exposed remains. Searches were performed in databases such as MEDLINE/PubMed, Scopus, ScienceDirect, Dialnet, Redalyc, the Spanish National Research Council (CSIC), and RECyT, including original research articles in English and Spanish that specifically addressed the effects of heat on human tooth structure and DNA recovery. Main body The findings underscore the thermal resistance of enamel, dentin, and cementum as key factors in safeguarding DNA. High temperatures cause various forms of molecular damage to DNA, such as strand breaks and base modifications. Despite these effects, dentin and cementum continue to yield amplifiable DNA, with mitochondrial DNA demonstrating greater thermal stability than nuclear DNA. Additionally, both the intensity and duration of heat exposure are critical determinants of DNA recovery quality. Conclusion Teeth are highly reliable sources of DNA in forensic contexts involving heat exposure. Although nuclear DNA is vulnerable, dentin and cementum, particularly their mitochondrial content, consistently provide viable genetic material. This review highlights the urgent need for standardized protocols for thermal exposure, DNA extraction, and result reporting to optimize DNA recovery from heat-exposed remains and enhance its forensic applicability.